Exercício e Insuficiência Cardíaca com Fração de Ejeção Preservada: foco no paradigma inflamatório - Eliane Rodrigues Cabral de Moraes Jaconiano (2021)
Background: Heart failure with preserved ejection fraction (HFpEF) is currently lacking an effective pharmacological treatment with impact on morbidity and mortality. Exercise training (EXT) is recognized as an important nonpharmacological tool, capable of improving exercise capacity and quality of life. There is also observational data supporting that those patients with greater levels of physical activity have a lower risk of hospitalization and cardiovascular mortality. However, the mechanisms underlying the beneficial effects of EXT in HFpEF are poorly comprehended. Purpose: This work intends to explore the hypothesis that the benefits of exercise training in HFpEF patients could be, at least in part, due to its modulating effects over the inflammatory paradigm described for this syndrome. Methods: We first conducted a literature search using PubMed-NCBI database to review the effects of EXT throughout each step of the pathophysiological pathway leading to HFpEF. Due to the scarcity of studies in the HFpEF population, the literature search included preclinical findings and clinical evidence from patients with HF irrespective of subtype as well as patients with some of the most common comorbidities in HFpEF. Then, in the second part of this thesis, we present an experimental study using ZSF1 obese rats as an animal model for HFpEF, designed to investigate whether exercise training reduces myocardial microvascular inflammation, rarefaction, hypertrophy and fibrosis, all of which are implicated in the pathophysiology of HFpEF. For that purpose, we resorted to left ventricle samples of sedentary and exercised rats and performed western blot analysis to quantify the expression levels of myeloperoxidase (MPO), intercellular adhesion molecule 1 (ICAM-1) and platelet/endothelial cell adhesion molecule 1 (PECAM-1). We also conducted a histological analysis to determine the effect of exercise on cardiomyocytes' cross-sectional area as well as myocardial collagen content. Results: Until the moment we performed our review, there were a very limited number of clinical studies assessing the molecular changes promoted by exercise training in HFpEF patients . Thus, there is currently no data to confirm or refute the impact of EXT in the modulation of the inflammatory paradigm and future studies should specifically explore this gap. However, EXT proved to be capable in modulating systemic inflammation, endothelial dysfunction and myocardial stiffness in preclinical studies as well as in patients with comorbidities also commonly found in HFpEF. Regarding our experimental work, it revealed a reduction in myocardial collagen (p <0.05) in the exercised rats compared with the controls. No significant changes were noted for cardiomyocytes' cross-sectional area as well as for MPO, ICAM-1 and PECAM-1 expression. Conclusion: There is rationale to support the hypothesis that EXT modulates crucial aspects of the inflammatory pathway described for HFpEF and future investigation on cellular and molecular mechanisms are encouraged.